2022
DOI: 10.2174/1570180819666220110145659
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Functional Derivatives of thiazolo[ 2,3-c][1,2,4]triazoles

Abstract: Background: Condensed triazoles are a well-known class of heterocyclic compounds due to a wide range of biological activity. The study is dedicated to the evaluation of the antimicrobial potential of new functional derivatives of thiazolo[2,3-c][1,2,4]triazoles. Methods: Effective, easy-to-implement and low-cost routes to the production of title compounds via electrophilic intramolecular heterocyclization are reported. Bactericidal and fungicidal activities against Gram-positive and Gram-negative bacteria, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For example, Li and Wu, who combined triazoles with pyrimidine, both obtained compounds with good antibacterial activity [25]. Slivka et al synthesized several compounds with triazole, thiazole and phenol substituents and their copper complexes, and the synthesized compounds had good fungicidal activity [26]. We found that most triazole pesticides are derivatives in which the nitrogen atom of the triazole ring is substituted by alkyl or aralkyl.…”
Section: Introductionmentioning
confidence: 89%
“…For example, Li and Wu, who combined triazoles with pyrimidine, both obtained compounds with good antibacterial activity [25]. Slivka et al synthesized several compounds with triazole, thiazole and phenol substituents and their copper complexes, and the synthesized compounds had good fungicidal activity [26]. We found that most triazole pesticides are derivatives in which the nitrogen atom of the triazole ring is substituted by alkyl or aralkyl.…”
Section: Introductionmentioning
confidence: 89%